UPAYA MENINGKATKAN KREATIVITAS BELAJAR SISWA MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK - Fransiska Kusuma Ningrum; Giyono Giyono; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine the increasment of creative learning after attending group counseling services in students of class XII SMK SPP Lampung District academic year 2012/2013. The problem in this study was the low student’s creativity. Its sentence in this study was